Rinsing with Statherin-Derived Peptide Alters the Proteome of the Acquired Enamel Pellicle - Taira, Even Akemi; Ferrari, Carolina Ruis; Carvalho, Gabriel; Ventura, Talita Mendes Oliveira; Martini, Tatiana; Dionizio, Aline Salgado; Araújo, Tamara Teodoro; Crusca, Edson [UNESP]; Marchetto, Reinaldo [UNESP]; Buzalaf, Marília Afonso Rabelo (Karger Publishers, 2021)
Changes in the proteomic profile of the acquired enamel pellicle (AEP) formed for 3 min or 2 h after rinsing with a peptide containing the 15 N-terminal residues of statherin, with serines 2 and 3 phosphorylated (StatpSpS), were evaluated. Nine volunteers participated in 2 consecutive days. Each day, after professional tooth cleaning, they rinsed for 1 min with 10 mL of phosphate buffer containing 1.88 × 10-5 M StatpSpS or phosphate buffer only (control). The acquired pellicle formed on enamel after 3 min or 2 h was collected with electrode filter papers soaked in 3% citric acid. After protein extraction, samples were analyzed by quantitative shotgun label-free proteomics. In the 3-min AEP, 19 and 131 proteins were uniquely identified in the StatpSpS and control groups, respectively. Proteins typically found in the AEP were only found in the latter. Only 2 proteins (neutrophil defensins) were increased upon treatment with StatpSpS, while 65 proteins (among which are several typical AEP proteins) were decreased. In the 2-h AEP, 50 and 108 proteins were uniquely found in StatpSpS and control groups, respectively. Hemoglobin subunits and isoforms of keratin were only found in the StatpSpS group, while cystatin-C, cathepsin D, and cathepsin G, isoforms of heat shock 70 and protocadherin were exclusively found in the control group. In addition, 23 proteins were increased upon treatment with StatpSpS, among which are histatin-1, serum albumin, and isoforms of neutrophil defensin and keratin, while 77 were decreased, most of them were typical AEP proteins. In both evaluated periods, rinsing with StatpSpS profoundly changed the proteomic profile of the AEP, which might impact the protective role of this integument against carious or erosive demineralization. This study provides important insights on the dynamics of the protein composition of the AEP along time, after rinsing with a solution containing StatpSpS.
Keywords: Acquired pellicle; Enamel; Erosive tooth wear; Proteomics; Statherin